Interactive radio’s promising role in climate information services: Farm Radio International concept paper - Perkins, Kevin; Huggins-Rao, Sheila; Hansen, James; Mossel, J. van; Weighton, L.; Lynag, S. (2015)
This paper focuses on how interactive radio programming can increase the reach of weather and seasonal climate information and related advisory services. In doing so, they can enhance small-scale farmers’ capacity to make optimal decisions and manage risks based on a better understanding of probabilistic seasonal forecasts. The objective is to outline strategy that could vastly and affordably expand the number of small-scale farmers that are reached by and benefit from weather and climate information and related advisory services. Building on Farm Radio International’s (FRI) pioneering African Farm Radio Research Initiative (AFRRI), we assess the opportunities for interactive radio to provide integrated climate and advisory information while increasing farmers’ equitable access to salient and legitimate programming. We describe a number of practical strategies that can be used to make radio-based climate communication interactive, outline elements of a successful interactive radio service targeting rural communities, and discuss costs and other issues required for sustainability.